Conformational stability of peroxidase from the latex of Artocarpus lakoocha: influence of pH, chaotropes, and temperature - Sonkar, Kirti Shila; Pachauri, Manendra; Kumar, Amit; Choudhary, Himanshi; Jagannadham, Medicherla V. (Frontiers in Plant Science, 2024)
The latex of the medicinal plant Artocarpus lakoocha (A. lakoocha), which has been shown to have potential anti-inflammatory and wound-healing capabilities, contains a novel hemeperoxidase. This protein was subjected to activity assays, fluorescence spectroscopy, and far-UV circular dichroism to investigate its structure, dynamics, and stability. The results demonstrated the presence of three folding states: the native state (N) at neutral pH, intermediate states including molten globule (MG) at pH 2 and acid-unfolded (UA) at pH 1.5 or lower, and acidrefolded (A) at pH 0.5, along with alkaline denatured (UB) at pH 8-12 and the third denatured state (D) at GuHCl concentrations exceeding 5 M. Absorbance studies indicated the presence of loosely associated form of heme in the pH range of 1-2. The protein showed stability and structural integrity across a wide pH range (3-10), temperature (70 °C), and high concentrations of GuHCl (5 M) and urea (8 M). This study is the first to report multiple 'partially folded intermediate states' of A. lakoocha peroxidase, with varying amounts of secondary structure, stability, and compactness. These results demonstrate the high stability of A. lakoocha peroxidase and its potential for biotechnological and industrial applications, making it a valuable model system for further studies on its structure-function relationship.